2017
DOI: 10.5935/0946-5448.20170024
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular Schwannoma and Ipsilateral Endolymphatic Hydrops: An Unusual Association

Abstract: Vestibular schwannoma and endolymphatic hydrops are two conditions that may present with similar audio-vestibular symptoms. The association of the two in the same patient represents an unusual finding that may lead clinicians to errors and delays in diagnosis and clinical management of affected subjects. We discuss the case of a patient with an intrameatal vestibular schwannoma reporting symptoms suggestive for ipsilateral endolymphatic hydrops. The patient presented with fluctuating hearing loss, tinnitus, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Diagnosis should always include brain magnetic resonance imaging to exclude concurrent retrocochlear conditions i.e. vestibular schwannoma 69,70 and further characterize the neuroanatomical basis of the auditory deficit 19 .…”
Section: Clinical Management Of Patients With Alzheimer's Disease and Hearing Lossmentioning
confidence: 99%
“…Diagnosis should always include brain magnetic resonance imaging to exclude concurrent retrocochlear conditions i.e. vestibular schwannoma 69,70 and further characterize the neuroanatomical basis of the auditory deficit 19 .…”
Section: Clinical Management Of Patients With Alzheimer's Disease and Hearing Lossmentioning
confidence: 99%
“…It has also been suggested that some patients with VS also suffer from dysfunctions of the secretion and resorption of endolymphatic liquid, potentially with associated hydrops ( 34 ) due to the inflammatory process occurring around the vestibular schwannoma ( 35 ). None of our subjects displayed an abnormal vHIT result with a normal caloric test result.…”
Section: Discussionmentioning
confidence: 99%
“…Although many hypotheses have been presented in the present literature to explain the mechanisms underlying the SNHL induced by VSs, its pathogenesis is likely multifactorial and remains debated. Among the possible explanations proposed include mechanical compression by VSs on the auditory nerve or the labyrinthine artery (Lassaletta et al 2019), ototoxic and neurotoxic VS-biological secretions (Dilwali et al 2015; Lassaletta et al 2019) as well as the presence of ELH (Roosli et al 2012; Hizli et al 2016; Eliezer et al 2019; Karch-Georges et al 2019), which has been described by radiological studies and histological reports of temporal bones, but has been rarely reported in the clinical practice, mostly in case reports (Ralli et al 2017).…”
Section: Discussionmentioning
confidence: 99%